Moderating Effects of Culture in Transfer of Knowledge: A Case of Danish Multinationals and their Subsidiaries in P.R. China and India - Verner Worm; Xiaojun Xu; Jai b.P. Shinha (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2005)
By drawing on a selective review of literature, we propose that the culture of Danish multinationals and transnational organizations interface with the Chinese and Indian societal and managerial cultures in order to create hybrid cultures in Danish subsidiaries in P. R. China and India. The hybrid culture moderates the relationships between the forms of knowledge and internationalization of multinationals on one hand and the transfer of knowledge on the other. It is postulated that stable cultural frames of the Danes and Chinese managers, both having stable cultural frame, will require long drawn efforts to overcome the cultural distance and transfer the various forms and levels of knowledge in the initial years of the subsidiaries. On the other hand, Indians' style of switching their cultural frames will create less entry problems but more recurring problems once Danish multinationals will get going. Once the postulates are empirically validated, potential implications for strategic interventions are briefly discussed. Keywords: Knowledge transfer, culture, MNCs.
hdl:10398/7400
Keywords: 330